2023
DOI: 10.1152/japplphysiol.00739.2022
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A receptor inhibition increases nitric oxide-dependent vasodilation independent of superoxide in non-Hispanic Black young adults

Abstract: Young non-Hispanic Black adults have reduced microvascular endothelial function compared with non-Hispanic White counterparts, but the mechanisms are not fully elucidated. The purpose of this study was to investigate the effect of endothelin-1 A receptor (ETAR) and superoxide on cutaneous microvascular function in young non-Hispanic Black (n=10) and White (n=10) adults. Participants were instrumented with four intradermal microdialysis fibers: 1) lactated Ringer's (control), 2) 500 nM BQ-123 (ETAR antagonist),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 68 publications
7
10
0
Order By: Relevance
“…The plateau phase of the local heating response is largely mediated by NO derived from eNOS (~60%-80%) (Bruning et al, 2012;Choi et al, 2014;Kellogg Jr., Liu, et al, 1999;Kellogg Jr. et al, 2008, 2009Minson et al, 2001). Consistent with data from our lab and others (Akins et al, 2022;Hurr et al, 2018;Kim et al, 2018;Kim & Brothers, 2020;Miller et al, 2021;Patik et al, 2018;Turner, Hayat, et al, 2023;Wolf et al, 2020;Wong et al, 2020), we found there is both reduced microvascular endothelial-dependent vasodilation (plateau; Figures 1 and 2) and reduced NO-dependent vasodilation (Figures 3 and 4) to a standardized local heating protocol in non-Hispanic Black young adults. Reduced microvascular…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The plateau phase of the local heating response is largely mediated by NO derived from eNOS (~60%-80%) (Bruning et al, 2012;Choi et al, 2014;Kellogg Jr., Liu, et al, 1999;Kellogg Jr. et al, 2008, 2009Minson et al, 2001). Consistent with data from our lab and others (Akins et al, 2022;Hurr et al, 2018;Kim et al, 2018;Kim & Brothers, 2020;Miller et al, 2021;Patik et al, 2018;Turner, Hayat, et al, 2023;Wolf et al, 2020;Wong et al, 2020), we found there is both reduced microvascular endothelial-dependent vasodilation (plateau; Figures 1 and 2) and reduced NO-dependent vasodilation (Figures 3 and 4) to a standardized local heating protocol in non-Hispanic Black young adults. Reduced microvascular…”
Section: Discussionsupporting
confidence: 89%
“…endothelial function and NO-dependent vasodilation is observed whether local heating to 39°C is used, as in the current study (Akins et al, 2022;Hurr et al, 2018;Kim & Brothers, 2020;Miller et al, 2021;Patik et al, 2018;Turner, Hayat, et al, 2023;Wong et al, 2020), or to 42°C (Kim et al, 2018). The increase in microvascular endothelial function and NO-dependent vasodilation at tempol compared to control sites suggests superoxide negatively affects the microvascular endothelium in non-Hispanic Black young adults.…”
Section: Non-hispanic Black Non-hispanic Whitesupporting
confidence: 54%
See 2 more Smart Citations
“…Black young adults (Turner, Hayat et al, 2023) or naturally cycling women during menstruation (Turner, Stanhewicz, Nielsen, Otis et al, 2023), suggesting that there is a complex interplay in mechanisms that result in a given percentage of maximal CVC in response to a local heat stimulus. For these reasons, we would suggest that it is important to assess a general measure of endothelial function (i.e., plateau) in addition to the NO contribution.…”
mentioning
confidence: 99%